Comportamiento organizacional y su repercusión en el crecimiento empresarial de la hacienda Florencia del recinto Mata de Cacao - Loza Bejarano, Valeria Rosa (2021)
he present case study focuses on determining the influence of organizational behavior on the business growth of the florence farm in the cacao plant area the study was carried out through descriptive research and its subsequent analysis, which allowed us to know the characteristics of the variables to investigate, and be aware of the current situation of the agricultural estate, allowing to establish the pertinent solutions taking the necessary corrections, to visualize the success and business growth of the company. to carry out this research, the survey is used as an instrument to carry out the research, which is applied to the people involved in the organization, in this case its administrator, secretary and plant manager. in such a way that organizational behavior is considered as a set of systematic operations that will be applied from activities such as the skill of the model to be used, data collection, detection of problems, encouraging staff, evaluation of results, that is, actions that allow the identification of the problem and the establishment of results with the sole purpose of improving human relations, the business economy and the execution of correct leadership, leading the company to unbeatable growth